Penurunan Kandungan Minyak/Lemak, BOD (Biochemical Oxygen Demand), dan TSS (Total Suspended Solid) pada Air Limbah Bengkel Mobil dengan Menggunakan Aerasi dan Sedimentasi - Fathonah, Haqul Fathonah; Mukhlis, Mukhlis; Afridon, Afridon; Mahaza, Mahaza; Awaluddin, Awaluddin (Jurnal Kesehatan Lingkungan Mandiri, 2023)
Researchers conducted research on car repair business activities to see the negative impacts on the liquid waste produced which is mixed liquid waste. One of the control efforts is to use aeration and sedimentation methods. This research aims to determine the reduction in oil/fat content, BOD (Biochemical Oxygen Demad) and TSS (Total Suspended Solid) in car repair shop wastewater using aeration and sedimentation in 2023. The research carried out is experimental, the object to be studied is wastewater car repair shop at PT Capella Padang using a simple tool designer using three buckets with each bucket 25 liters. The results of the study showed that there were differences in oil/fat and TSS, before treatment the results of fatty oil were 12 mg/l, BOD 32 mg/l and TSS 107 mg/l after using a simple tool and given nine repetitions, the oil/fat results were 0.4. mg/l, 73.2 mg/l and TSS 12.1 mg/l. In conclusion, the efficiency value after treatment experienced a significant decrease in oil/fat, 96%, BOD efficiency value - 1.23%, while TSS experienced a significant decrease, namely 88%. It is hoped that for further research using aeration and sedimentation, better results will be obtained in accordance with the regulations of the Minister of Environment of the Republic of Indonesia Number 68 of 2016 concerning Waste Water Quality Standards and also as knowledge, information and guidance for health polytechnic students.